Particular Features of the Revenue and Expenditure in Tourism Activities of Travel Agencies - SIMIONESCU, Silvia (Journal of Environmental Management and Tourism, 2016)
The formation, structure and size of expenditures and revenues depend heavily on technological and organizational and technical peculiarities, and the industry in which the entity. This finding explains why entities varies from one industry to another and even within the same industry which, whether in certain types of expenditure and revenue, whether it generates economic operations have a different weight which leads to structure and different size of expenditure and revenue.
Keywords: revenues; expenses; travel; travel agency; services; tourism activities; brokerage operations